2007
DOI: 10.1248/jhs.53.302
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activation of Valproate Glucuronidation by Carbapenem Antibiotics

Abstract: The serum concentration of valproic acid (VPA) in epilepsy patients decreased by the administration of carbapenem antibiotics, such as meropenem, panipenem or imipenem, to a sub-therapeutic level. Studies to explain the decrease were carried out using almost rats by the following steps: absorption of VPA in the intestine, glucuronidation in the liver, disposition in blood and renal excretion. It is difficult to consider the inhibition of intestinal absorption, because carbapenem antibiotics are intravenously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Fortunately, for patients with infectious diseases, TBM is available without cilastatin, which blocks the hydrolysis of carbapenems in kidneys, owing to the stability to dehydropeptidase 1 (drug's interview form, Meiji Seika Pharma Co., Ltd., Japan). Additionally, TBM has been reported to scarcely interact with CYP3A4 and CYP2B6 (28,29). More importantly, TBM has been proved to exhibit good distribution into the pulmonary epithelial lining fluid in an animal model, which allows TBM to be used for lung disease (28).…”
mentioning
confidence: 99%
“…Fortunately, for patients with infectious diseases, TBM is available without cilastatin, which blocks the hydrolysis of carbapenems in kidneys, owing to the stability to dehydropeptidase 1 (drug's interview form, Meiji Seika Pharma Co., Ltd., Japan). Additionally, TBM has been reported to scarcely interact with CYP3A4 and CYP2B6 (28,29). More importantly, TBM has been proved to exhibit good distribution into the pulmonary epithelial lining fluid in an animal model, which allows TBM to be used for lung disease (28).…”
mentioning
confidence: 99%
“…It has been reported that P-glycoprotein and multidrugresistance-associated protein 2 might play a role in the renal excretion of valproic acid glucuronide. 22 However, Mori and Mizutani 22 argued that the activation of P-glycoprotein and multidrug-resistance-associated protein 2 for transport of valproic acid glucuronide could not be found by preincubation with carbapenem in vitro. Therefore, other transporters might be responsible for excreting valproic acid glucuronide from the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the interaction between VPA and CBPMs, the following mechanisms have been proposed: 1) inhibition of intestinal VPA absorption by CBPMs (Torii et al, 2001(Torii et al, , 2002, 2) interruption of enterohepatic circulation of VPA by CBPMs (Kojima et al, 1998), 3) increased partition of VPA into erythrocytes by CBPMs (Omoda et al, 2005;Ogawa et al, 2006), 4) elevation of UDP-GA levels by CBPMs (Yamamura et al, 1999(Yamamura et al, , 2000, 5) induction of UGT by CBPMs (Mori and Mizutani, 2007), and 6) inhibition of deconjugation of VPA-glucuronide (VPA-G) by CBPMs (Nakajima et al, 2004;Nakamura et al, 2008). However, most of the previously proposed mechanisms (mechanisms 1-5) may not solely explain the interaction observed under clinical conditions for the following reasons: with mechanism 1, the interaction observed after intravenous administration of VPA (Clause et al, 2005;Coves-Orts et al, 2005;Spriet et al, 2007) cannot be accounted for.…”
Section: Introductionmentioning
confidence: 99%